Exploring Nurses’ Meaning and Experiences of Compassion: An International Online Survey Involving 15 Countries - Papadopoulos, Irena; Taylor, Georgina; Ali, Sheila; Aagard, Magdeline; Akman, Ozlem; Alpers, Lise-Merete; Apostolara, Paraskevi; Biglete-Pangilinan, Sylvia; Biles, Jessica; García, Angel Martin; González-Gil, Teresa; Koulouglioti, Christiana; et al. (My University, 2017)
Purpose: In recent years, there has been much focus on compassion in nursing care, and concern has been raised in a number of reports and media stories regarding decreased compassion. The aim of this study was to explore similarities and differences in the understanding and demonstration of compassion in nursing practice across 15 countries. Design: A total of 1,323 nurses from 15 countries responded to questions in relation to compassion, via an international online survey. Results: The data revealed the impact of sociopolitical influences on perceptions of compassion, and the conscious and intentional nature of compassion. Discussion and Conclusion: The study demonstrated shared understandings of the importance of compassion as well as some common perceptions of the attributes of compassionate care. The differences reported were not as significant as had been expected. Implications for Practice: Further research is needed to explore the country and culture differences in the enactment of compassion.
Keywords: Compassion; Cultural competence; Culture; Transcultural nursing